Local therapy with Vagifem in women treated for endometrial and uterine cervical cancer - Markowska, Janina; Kurczab, Renata; Grabowski, Jacek (Menopause Review/Przegląd Menopauzalny, 2006)
Atrophic vaginitis and urinary incontinence significantly affect life quality of perimenopausal patients who have undergone brachytherapy for endometrial and uterine cervical cancer. The aim of our study was to evaluate the efficacy of local Vagifem therapy in treatment of these diseases. We have observed that use of Vagifem brings relief of symptoms in atrophic vaginitis, but less so in urinary incontinence. Use of Vagifem does not increase risk of cancer recurrence from an oncological point of view.